Present and Future Perspectives on Therapeutic Options for Carbapenemase-Producing Enterobacterales Infections - Vrancianu, Corneliu Ovidiu (Microorganisms, 2021)
Carbapenem-resistant Enterobacterales (CRE) are included in the list of the most threatening antibiotic resistance microorganisms, being responsible for often insurmountable therapeutic issues, especially in hospitalized patients and immunocompromised individuals and patients in intensive care units. The enzymatic resistance to carbapenems is encoded by different β-lactamases belonging to A, B or D Ambler class. Besides compromising the activity of last-resort antibiotics, CRE have spread from the clinical to the environmental sectors, in all geographic regions. The purpose of this review is to present present and future perspectives on CRE-associated infections treatment.